Home pelvic floor muscle training with electromyographic biofeedback to treatment of the urinary incontinence: A prospective analysis - Yılda Arzu Aba; Deniz Sarıcı; Ramazan Özyurt; Bulat Aytek Şık (Journal of Contemporary Medicine, 2019)
AbstractAim: Pelvic floor muscle training is an accepted therapy to improve or cure symptoms of urinary incontinence. In this study, examination of short term changes in home treatment of pelvic floor muscle training with FemiScan Home Trainer in treatment of urinary incontinence was aimed.